Potential CO2-production in aerobic conditions from a Siberian tundra environment - Bolter, Manfred; Muller-Lupp, Wiebke; Takata, Kumiko; Yabuki, Hironori; Moller,Rolf (National Institute of Polar Research, 2003)
P(論文) Soil respiration was analysed from different soil profiles of an arctic tundra environment (Samoylov Island, Lena Delta, East Siberia) during field studies in 1998 and 1999. Samples from discrete soil layers (0-47 cm), from the soil surface down to the permafrost table, were incubated and analysed for CO_2-evolution at different temperatures, related to ambient values (0°C to 20°C) in a dynamic chamber system. The soil investigated was located in a low-centre polygon on a poorly drained peat terrace and determined as a Glacic Aquiturbel. Soil respiration data from the individual layers of this location were combined with soil temperature measurements of a comparable tundra environment near Tiksi. These data were split into discrete intervals of 5°C which were regarded as intervals for different levels of soil microbial activity. Time spans for these temperature ranges were calculated and used as a base for further calculations of potential seasonal CO_2-emissions. Changing patterns of soil respiration could be related to varying substrate conditions and effects of physical factors, especially freezing and thawing. They are regarded as important factors controlling CO_2-flux from tundra soils. High levels of CO_2-evolution can be attributed to soil layers where high amounts of organic matter are available, oxygen penetrates through soil pores and elevated temperatures above 0°C maintain metabolic processes. departmental bulletin paper